2014
DOI: 10.3390/ijms151018693
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias and Sleep-Disordered Breathing in Patients with Heart Failure

Abstract: The relationship between heart failure (HF), sleep-disordered breathing and cardiac arrhythmias is complex and poorly understood. Whereas the frequency of predominantly obstructive sleep apnea in HF patients is low and similar or moderately higher to that observed in the general population, central sleep apnea (CSA) has been observed in approximately 50% of HF patients, depending on the methods used to detect CSA and patient selection. Despite this high prevalence, it is still unclear whether CSA is merely a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
16
0
3
Order By: Relevance
“…In our study, there is a significant relation with poor sleep quality and the prevalence of VT in patients with AMI. Consistently, it has been found that central sleep apnea is significantly linked with VT/VF in chronic heart failure, which is the most frequent cause of sudden cardiac death in those patients 16,17. In addition, SDs have been shown to cause the worsening of clinical outcomes in AMI patients 18.…”
Section: Discussionmentioning
confidence: 65%
“…In our study, there is a significant relation with poor sleep quality and the prevalence of VT in patients with AMI. Consistently, it has been found that central sleep apnea is significantly linked with VT/VF in chronic heart failure, which is the most frequent cause of sudden cardiac death in those patients 16,17. In addition, SDs have been shown to cause the worsening of clinical outcomes in AMI patients 18.…”
Section: Discussionmentioning
confidence: 65%
“…However, many patients with cardiovascular dysfunction also have respiratory disorders. The occurrence of central sleep apnea has been demonstrated to be relative to clinical outcomes, atrial arrhythmia, or ventricular arrhythmia in patients with heart failure [ 2 , 3 , 19 ]. Moreover, the autonomic nervous system and respiratory control system have a reciprocal interaction.…”
Section: Resultsmentioning
confidence: 99%
“…More than nearly half of HF patients (with either retained or decreased ejection fraction) have SDB, which is about ten times the population average [4,[8][9][10]. In the absence of indications, such as prolonged daytime sleepiness, screening for SDB is not usually done in HF patients [1]. Therefore, in patients with HF, sleep apnea remains a widely underdiagnosed disorder [1].…”
Section: Introductionmentioning
confidence: 99%